Multiprofessional Health Residency Programs in the formation of priority health care networks - Pinto, Tiago Rocha; Cyrino, Eliana Goldfarb [UNESP] (FapUNIFESP (SciELO), 2022)
This study analyzed the integration of multiprofessional health residency programs (MHRPs) with the formation of public health networks within the scope of the Brazilian National Health System (SUS). We carried out a qualitative study drawing on the actor-network theory and controversy mapping. We conducted semi-structured interviews with 23 residents from different professions undergoing the second year of MHRPs. The results were categorized into four core areas: 1. Perspectives on experience in the MHRPs; 2. From the particularity of the core professional area to interprofessionality in the field of action; 3. Obstacles and weaknesses in the production of care networks; and 4. MHRPs in the formation of health networks. The findings show that MHRPs facilitate the operationalization of health care networks in Brazil, demonstrating their importance for professional training integrated with the SUS and tailored to the population’s health needs.
Los Programas de Residencia Multiprofesional en Salud en la conformación de las redes prioritarias de atención
Os Programas de Residência Multiprofissional em Saúde na conformação das redes prioritárias de atenção
Keywords: Actor-network theory; Health care networks; Health education and training; Multiprofessional health residency; Primary health care